Pattern of Carcinoma of Oral Cavity at a Tertiary Care Center - Akhlaq, Humera (International Journal of Pathology, 2020)
Objective: To identify the distinct anatomical sites of the oral cavity those are susceptible to the occurrence of cancer among patients visiting a tertiary care hospital in Karachi, Pakistan. Methods: Around 329 participants were enrolled in this retrospective study which was completed at Jinnah Postgraduate Medical Centre in Karachi, Pakistan from January 2016 to December 2018. The data regarding the occurrence of different types of carcinoma in the oral cavity, site of the lesion along with the degree of differentiation for squamous cell carcinoma was reported in this study. Results: The participants enrolled in the study were mostly males i.e. 62% and only 38% were females. The mean age of the participants was 40.00 ± 16.84 (SD). Approximately, 179 participants tested positive for cancer while 150 were diagnosed with other conditions of the oral cavity. About 142 cases of squamous cell carcinoma were identified and only 1 case of papillary carcinoma was seen apart from other types of cancers. Most of the lesions were detected in the buccal mucosa (58%) followed by the lips (9%) and tongue (8%). Conclusion: It is evident from this study that cancer is predominantly seen in the buccal mucosa of the oral cavity with males being more highly susceptible than females.